Swelling Behavior of Cross-link PVA with Glutaraldehyde - Matty, Fadhel S.; Sultan, Maha T.; Amine, Adiba Kh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The polymeric hydrogels composed of poly vinyl alcohol (m.wt 72000) and glutaraldehyde(5%,8% and 10%) , have been thermally prepared for the purpose of studying their swelling and drug  release behavior .      The swelling ratio was measured for all the hydrogel samples at 37Â°C, in three different media pH (1.2, 4.7 and 6.8) as a function of time. The results show  that the maximum swelling ratios were arranged as follows :pH =6.8 >  pH =4.7 > pH =1.2 hydrogels cross linked PVA showed a typical pH  responsive behavior such as high pH has maximum swelling while low  pH  shows minimum swelling.